Non conventional water resources: present situation and perspective use for irrigation - Papadopoulos I. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
Most countries in the Near East, North Africa and South Europe are arid or semiarid. They have low rainfall, mostly seasonal and with erratic distribution. Moreover, due to the rapid development of urban and rural domestic water supplies, conventional water resources have been seriously depleted and wastewater reclamation and use for irrigation, among other non conventional water sources, gained increasing role in the planning and development of additional water supplies. In this respect, in most arid and semiarid countries, wastewater reclamation and reuse is viewed increasingly as a men to augment existing and future water resources against the growing demand for water. Reclaimed water is a reliable source even in drought years, and thus is capable to replacing potable water from non-potable water uses. Because of this, wastewater treatment and use for irrigation has been expanded considerably the last few decades. However, wastewaters are unique in composition, often associated with environmental and health risk and their acceptability to replace more conventional or other non-conventional water sources for irrigation is highly dependent whether the health risk and environmental impact are within acceptable levels. This paper elaborates the benefits and problems associated with non-conventional water resources with more emphasis on wastewaters and provide information on present reuse practices and their future prospective uses for irrigating agricultural crops, within acceptable levels of risk
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)